(untitled) (UNED Research Journal, 2017)
There are few studies on the diet of neo- tropical birds, including psittacines. The green macaw (Ara ambiguus) feeds on the seeds of the mountain almond tree (Dipteryx panamensis), titor (Sacoglottis trichogyna) and other species. However there are no reports of this species feeding on beach almond (Terminalia catappa). Here we inform that it uses leaves as a tools to feed on it. Its consump- tion could be due to the lack of fruits of D. panamensis and S. trichog- yna, and to the high nutritional value of the seed. Using the leaves to peel the pericarp can be a strategy to avoid its’ bitter taste.